Subjective Well-Being Pada Pasangan Yang Belum Memiliki Anak Kandung Tetapi Memiliki Anak Angkat - Anggita Sari, Septian, Rini Lestari, S.Psi, M.Si (2017)
ABSTRACT Commonly, a married couple has a dream to have offspring, but not all couples have offspring directly after their marriage. This research aims to explain the description of subjective well being in the couples who has no offspring but having adopted child and the factors which influence the subjective well being. Subjects of this research are three married couples who have no offspring but having adopted children in Karanganyar Regency. The technique of data collection used in this research is interview. The data analysis used the technique of interactive analysis. This research found that initially, the three subjects often undergo a negative affection and rarely feel a positive affection, but, by the presence of a child and supports from husband/wife and parents, they are able to make the subjects raised up from sadness. Besides, the subjects found their life satisfaction from the pleasant memories in the past, having a life goal, viewing her/himself positively and being grateful for what they have. The factors which influence the subjective well being in the subjects are the pleasant and sad memories, gratitude, sincerity and submission to the situation they face, support from family, a positive relationship to the husband/wife and the child, family's love, having a quality time together with family, and spending the spare time with the husband/wife and the child. Keywords: subjective well-being, couples who have no offspring, adopted child.